Problem-Based Learning In Indonesian Language Learning: A Literature Review From The Perspectives Of Education And Islamic Values - Chanti Santia Putri; Ahmad Suradi; Heny Friantary (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model in Indonesian language learning through a literature review approach. Problem-Based Learning is a learning model that emphasizes the active involvement of students in the process of solving real problems so that learning becomes more meaningful, contextual, and student-centered. The method used in this study is a literature review with a qualitative descriptive approach. Data were obtained from various scientific sources such as national journals, research articles, and relevant academic publications in the 2020–2025 period. Data analysis was conducted using content analysis techniques by collecting, classifying, and synthesizing the results of previous studies related to the application of PBL in Indonesian language learning. The results of the study indicate that the Problem-Based Learning model has high effectiveness in improving student learning outcomes, critical thinking skills, and language skills, especially in writing and speaking skills. In addition, Problem-Based Learning can also increase learning motivation, student activeness, and create a more interactive and collaborative learning atmosphere. However, the implementation of PBL still faces several challenges such as teacher readiness in designing learning, time constraints, and differences in student abilities. Overall, it can be concluded that the Problem Based Learning model is an effective and relevant learning model to be applied in Indonesian language learning in the 21st century education era.